ST-Elevation Myocardial Infarction: A Simulation Case for Evaluation of Interprofessional Performance in a Hospital - Hadiki Habib; Eka Ginanjar; Arif Mansjoer; Septo Sulistio; Imamul A. Albar; Radi M. Mulyana (Emergency Medicine International)
Introduction. Interprofessional collaboration between units in a hospital is essential in order to reach desired time for primary percutaneous intervention (PCI) in acute ST-Segment Elevation Myocardial Infarction (STEMI) cases. We developed a simulation to engage various medical and nonmedical staff in interprofessional and interunit team collaboration. Method. We used a scenario in this simulation. Beginning in the emergency department, it detailed a 50-year-old male presenting with progressive chest pain since 7 hours before admission. The emergency team directly examined the patient, and STEMI diagnosis was made, followed by sending the patient to the cardiac catheterization laboratory to undergo primary PCI. A resuscitation kit was required for the simulation. An evaluation sheet was prepared to evaluate every step of patient management. Three judges observed the simulation. At the end of the simulation, debriefing was done, and recommendation for the simulation was discussed. Besides medical activities during patient management, interprofessional communication, administration activities, consultations, and handover process were also evaluated. Results. The team achieved the appropriate door-to-electrocardiogram (ECG) time in 8 minutes, but overall target was delayed since door-to-skin puncture time was reached in 110 minutes. Some factors that contributed to these conditions were long waiting time during patient admission, several attempts for telephone consultation to the cardiologist, and prolonged admission process in the cardiac catheterization laboratory. Conclusions. The simulation was well received by both participant and our institution, stating that it is a valuable resource for developing interdisciplinary learning program. This simulation also contributed to the development of the clinical pathway, STEMI protocol, in our institution.